How will artificial intelligence and Industry 4.0 emerging technologies transform operations management?. Issue 12 (19th October 2022) - Mithas, Sunil; Chen, Zhi‐Long; Saldanha, Terence J.V.; De Oliveira Silveira, Alysson
Abstract: Emerging technologies such as artificial intelligence, blockchain, additive manufacturing, advanced robotics, autonomous vehicles, and the Internet of Things are frequently mentioned as part of "Industry 4.0." As such, how will they influence operations and supply chain management? We answer this question by providing a brief review of the evolution of technologies and operations management (OM) over time. Because terms such as "Industry 4.0" do not have a precise definition, we focus on more fundamental issues raised by Industry 4.0 emerging technologies for research in OM. We propose a theory of disruptive debottlenecking and the SACE framework by classifying emerging technologies in terms of the functionalities they enable: sense, analyze, collaborate, and execute. Subsequently, we review the nascent but rapidly growing literature at the interface between digital technologies and OM. Our review suggests that one way to assess the value of Industry 4.0 technologies can be via their influence on adding revenues, differentiating, reducing costs, optimizing risks, innovating, and transforming business models and processes. Finally, we conclude by proposing an agenda for further research.